Compensating the anisotropic mechanical properties of electron beam melting-based Gyroid scaffolds using structural design. (15th July 2022) - Peng, Xing; Huang, Qiyuan; Zhang, Guoxian; Li, Junyan; Zhang, Xiaogang; Lu, Yongtao; Jin, Zhongmin
Highlights: A structural design method was used to compensate for the anisotropic mechanical response of scaffolds produced by EBM process. Combining experimental and FE methods to decouple the contributions of geometric discrepancy and powder bonding status to the anisotropic mechanical response of scaffolds. The effect of structural design on the prediction of geometry and mechanical discrepancies was evaluated. Abstract: In recent years, scaffolds based on triply periodic minimal surface (TPMS) have been identified as one of the candidates for bone repair materials because of their excellent mechanical and biological properties. In addition, additive manufacturing (AM) enables the production of porous scaffolds with complex microstructures. However, some AM methods (e.g., electron beam melting, EBM) tend to produce a significant anisotropic discrepancy in the mechanical response of scaffolds, and neither the underlying mechanisms nor the compensation method for this discrepancy is clear so far. The aim of this study was to compensate for this discrepancy using structural design and to reveal the underlying mechanisms of each impact factor. Four types of Gyroid scaffolds ranging from rotational symmetric to obvious anisotropic were produced along the height direction of the scaffold using EBM technique, and the relationship between the degree of structural anisotropy ( DA ) and compressive modulus was determined. When the value of DA was 1.08, the compressive modulus in the building and non-building directions were equal, which means that the anisotropic mechanical discrepancy generated by EBM process was compensated. On the other hand, the decoupling of factors affecting mechanical properties showed that the effective compressive modulus of the rotational symmetric scaffold in the building direction was 42.6% lower than that of non-building direction in the finite element model with highly reductive geometry, while the discrepancy in experimental method was only 20%. The results suggest that the geometric discrepancy is the main factor of the mechanical discrepancy, and the orientation of columnar grains is inclined to the building direction which helps to alleviate the mechanical anisotropy caused by geometry discrepancy. The findings of this study provide important information for the application of TPMS scaffolds in bone implants. Graphical abstract: Image, graphical abstract